A study on the perception of school discipline by the secondary school teachers of Sri Lanka - Dharmawardana, H.M.K.C. (My University, 1993)
The present study was designed to measure the perception of school discipline by secondary school teachers of Sri Lanka, to assess the status of discipline prevailing in schools, and to determine the factors that impinge on school discipline. six different constructs of school discipline were indentified from literature. These were, 'school discipline is' (a) direct authoratative control of pupil behaviour or conduct;...